(untitled) (International journal of artificial intelligence, 2024)
The article deals with the urgent problem of energy saving in agriculture, in particular, when using induction motors in forage chopping plants. The authors analyze electricity consumption in agriculture in Uzbekistan and note a significant share of electric motors in the total volume of energy consumption. Reactive power compensation using static capacitors is proposed as a method to improve energy efficiency. The authors describe the compensation method, provide a formula for calculating the capacitance of capacitors and evaluate the effectiveness of the method on the basis of experimental studies.